Gender responsive communication tools and approaches for scaling the Triple S Technology in Ethiopia and Ghana - Mayanja, S.; Suleiman, I.; Imoro, S.; Mourik, Tom A. van; Asfaw, F.; Cherinet, M.; McEwan, M. (International Potato Center, 2020)
The RTB Triple S Scaling project (3S+) is a 27-month project funded by the CGIAR Research Program on Roots, Tubers and Bananas (RTB) and was operational in Ghana and Ethiopia. The aim of the project was to scale out the Triple S technology – a root-based vine production technology suitable for arid and semi-arid areas. Amongst the scaling strategies developed and implemented, was an outreach strategy based on three types of treatment: Core communities, informed communities, spillover communities. Subsequently, various communication tools and approaches were used for the three types of communities. Following use of these strategies, there was a need to assess their effectiveness in aiding technology dissemination, uptake and scaling. A study was designed to assess which communication methods were best suited to the needs of women and men in transmission and delivery of the Triple S innovation scaling package.